Investigation of turbulence flow characteristics in a dual-mode scramjet combustor using hydroxyl tagging velocimetry. (April 2019) - Ye, Jingfeng; Shi, Deyong; Song, Wenyan; Li, Guohua; Zhang, Zhenrong; Hu, Zhiyun
Abstract: The results of an investigation of the turbulence characteristics of a kerosene-fueled, dual-mode scramjet combustor are reported in this paper. The combustor had a cavity flame holder and was operated at an inlet Mach number of 2. The combustor was made to transition across different modes by adjusting the fuel injection and inlet flow total temperature. The velocity and fluctuations thereof in the flow field upstream of the combustion zone were measured using the hydroxyl tagging velocimetry method. Given a signal-to-noise ratio of about 4 for the OH lines and considering the effect of dithering of the optical equipment owing to strong vibration, the uncertainty in the measured velocity was about 29 m/s. The computational fluid dynamics solution of the flow was compared with the measurements, and the computed positions of the shock wave trains were used to distinguish the combustion modes. The results show that the turbulence fluctuation velocity ( u' rms ) in the supersonic mode was the same as that in the case of the nonreacting flow, but it was considerably higher in the subsonic mode. During the ram-to-scram process, the turbulence intensity ( u' rms / ū ) declined exponentially as the local Mach number of the flow field upstream of the combustion zone increased. Highlights: The turbulence characteristics were measured in a scramjet combustor. The uncertainty in the measured velocity was about 29 m/s. The turbulence intensity decreases with the local Mach number increasing.